PENGARUH RASIO PROFITABILITAS PERUSAHAAN TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR SUB-SEKTOR INDUSTRI MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI - AYU WIJAYANTI, DYAH Ayu (Jurnal Akuntansi AKUNESA, 2013)
The purpose of this study was to determine the effect of the ratio of stock prices on theprofitability of the manufacturing sub-sectors food and beverage industry. Study usesfinancial statement data of manufacturing firms that go public in Indonesia period 2009-2011 with sample of 11companies listed in Indonesia Stock Exchange, analysis techniqueused multiple regression analysis. The researchhypotheses used T test and F test. The resultsshowed that simultaneously proved that the Net Profit Margin (NPM), Earning per Share(EPS), Return on Assets (ROA) and Return on Equity (ROE) have a significant effect on stockprices. And partially proved that the Return On Equity (ROE) has a significant negativeeffect on stock prices.This is possible because in assessing the company, investors stillconsider the company's ability returns to shareholders.Key words: Net Profit Margin (NPM), Earning per Share (EPS), Return on Assets (ROA),Return on Equity (ROE), stock price